AQUIFER MAPPING BASED ON STRATIGRAPHIC AND GEOELECTRICAL DATA ANALYSIS IN BEDOYO REGION, GUNUNG KIDUL REGENCY, YOGYAKARTA SPECIAL REGION - Fatimah Fatimah; Al Hussein Flowers Rizqi; Waskita Murti Bambang Yudhana (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2021)
The research area is a high karst area composed of carbonate rocks, where drought occurred almost every year. This study aimed to determine water availability in aquifer rocks by analyzing the surface geology and subsurface layers (geophysical method). We used the Schlumberger configuration in the geoelectric method at four locations in the study area to determine the resistivity value of the rocks beneath the surface. The results revealed that the site comprises tuff, crystalline limestone, layered limestone /chalky, and gravel to clay deposits. An aquifer was only found in Asem Lulang Village, which has a wedge layer with a thickness of 59 meters and thinned down to 5 meters towards the village of Ngalas Ombo. The value of the resistivity aquifer ranges from 0.18 to 9.18 ohm.m. The existence of that aquifer could indicate that the aquifer is only found in weakly undulated